2019
DOI: 10.1016/j.carres.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the reversible enzyme reaction of rabbit muscle glycogen phosphorylase b using isothermal titration calorimetry

Abstract: Glycogen phosphorylase enzymes (GP) catalyse reversible reactions; the glucose transfer from glycogen to inorganic phosphate (Pi, phosphorolysis) or the reverse glucose transfer from glucose-1-phosphate (G-1-P) to glycogen (synthesis). Rabbit muscle GPb (rmGPb) was used as a model enzyme to study the reversible enzyme reaction. To follow both directions of this reversible reaction, we have developed a novel isothermal titration calorimetry (ITC) method for the determination of the direct reaction rate. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…For example, glycosidase activity can be measured spectrophotometrically with synthetic substrates, such as maltooligomer derivatives with chromogenic chloronitrophenyl (CNP) groups attached (Klaus et al, 1999;Morishita et al, 2000;Ramasubbu et al, 2005). Separate studies on α-amylase and glycogen phosphorylase found the K m values of the fluorogenic substrate analogs to be substantially lower than those of the native substrates determined by ITC, possibly due to interactions of the chromophore with the active site of the enzyme (Lehoczki et al, 2016;Szabó et al, 2019). Thus ITC represents a simple way to accurately characterize how enzymes interact with their biologically relevant molecular partners.…”
Section: Discussionmentioning
confidence: 97%
“…For example, glycosidase activity can be measured spectrophotometrically with synthetic substrates, such as maltooligomer derivatives with chromogenic chloronitrophenyl (CNP) groups attached (Klaus et al, 1999;Morishita et al, 2000;Ramasubbu et al, 2005). Separate studies on α-amylase and glycogen phosphorylase found the K m values of the fluorogenic substrate analogs to be substantially lower than those of the native substrates determined by ITC, possibly due to interactions of the chromophore with the active site of the enzyme (Lehoczki et al, 2016;Szabó et al, 2019). Thus ITC represents a simple way to accurately characterize how enzymes interact with their biologically relevant molecular partners.…”
Section: Discussionmentioning
confidence: 97%
“…Radioactive measurements have been applied, requiring radioactive labeled substrates and special equipment [ 17 , 27 ]. Other authors have implemented methods to measure the glucose 1-phosphate released from glycogen degradation, using electrospray ionization mass spectrometry [ 28 ], high performance liquid chromatography (HPLC) [ 29 ], or isothermal titration calorimetry (ITC) [ 19 ] methods. However, there are two most frequently applied methods in the literature for measuring GP activity.…”
Section: Discussionmentioning
confidence: 99%
“…The second method, and most often cited in the literature, evaluates glycogen synthesis, which is based on the colorimetric determination of inorganic phosphate released from glucose 1-phosphate after the glucosyl transfer to glycogen molecule. The first method is not suited for inhibition studies due to potential side interactions between tested compounds and the different enzymes used, phosphoglucomutase and glucose 6-phosphate dehydrogenase [ 19 ]. The second method demonstrates relevant advantages, being less expensive due to the use of only one enzyme, and the formed product is easily detected and allows the straightforward investigation of the inhibitory effect of several compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations